1990
DOI: 10.1002/bjs.1800771212
|View full text |Cite
|
Sign up to set email alerts
|

Paraileostomy hernia: A clinical and radiological study

Abstract: Forty-six patients who underwent colectomy with end ileostomy for ulcerative colitis (n = 33) or Crohn's disease (n = 13) have been reviewed for paraileostomy hernia (PIH) formation 1-16 years after surgery. PIH developed in 13 of these patients (28 per cent) and was not related to the original disease or excessive weight gain. Twenty-eight patients underwent limited computed tomography (CT) scanning of the stomal region. Eight of these had a clinically detectable PIH, which was demonstrated on CT. A further t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(69 citation statements)
references
References 17 publications
(1 reference statement)
1
62
1
4
Order By: Relevance
“…In the present study over 25% of patients who had an ileosto my constructed for inflammatory bowel disease and were followed for a mean of 60 months, developed stomal com plications that were not amenable to conservative man agement and required ileostomy revision. This is in line with the experience of other centres [ 1,[3][4][5], The prepon derance of operations for Crohn's disease in our series reflects the referral pattern to our unit and the interest of the senior author in the surgical management of Crohn's disease. Ileostomy revision was required more frequently in patients with Crohn's disease than patients with ulcer ative colitis.…”
Section: Discussionsupporting
confidence: 72%
“…In the present study over 25% of patients who had an ileosto my constructed for inflammatory bowel disease and were followed for a mean of 60 months, developed stomal com plications that were not amenable to conservative man agement and required ileostomy revision. This is in line with the experience of other centres [ 1,[3][4][5], The prepon derance of operations for Crohn's disease in our series reflects the referral pattern to our unit and the interest of the senior author in the surgical management of Crohn's disease. Ileostomy revision was required more frequently in patients with Crohn's disease than patients with ulcer ative colitis.…”
Section: Discussionsupporting
confidence: 72%
“…Some studies define herniation as a palpable bulge at the ostomy site upon a Valsalva maneuver [15,16] while many other reports offer no definition at all [7,8,17,18]. The most common classification system describes four subtypes: type 1: interstitial hernia; type 2: subcutaneous hernia; type 3: intrastomal hernia; and type 4: peristomal hernia (stoma prolapse) (table 1).…”
Section: Definition and Incidencementioning
confidence: 99%
“…Although malnutrition and corticosteroid use are mentioned in many of the reviews as risk factors for the development of PH, to the best of our knowledge there is no study that confirms those clinically rational assumptions. Among surgical-related factors it is notable that the rate of PH is higher in colostomies compared with ileostomies and in end stomas as opposed to lateral stomas [12][13][14]. In addition, there is a great impact of the surgical technique involved in stoma creation.…”
Section: Risk Factor For the Development Of Phmentioning
confidence: 99%
“…When using an accurate measurement to create the trephine, the rate of PH dropped [17]. The correlation between the position of the stoma within the abdominal wall was studied by Sjodahl et al who demonstrated an advantage for enterostomy constructed through the rectus abdominis muscle [18], though in similar studies this association was not statistically significant [14,19,20]. One study has shown better results for extra-peritoneal positioning of the stoma, but there are no prospective randomized clinical trials comparing these two methods [13,19].…”
Section: Risk Factor For the Development Of Phmentioning
confidence: 99%